Pemberdayaan Santri dalam Pemaknaan Kitab Kuning Melalui 3 Bahasa - Hidayatullah, Fahmi; Rizal, Soni Samsu (Khidmat, 2021)
The purpose of this paper is to describe the entirety of independent community service activities at the Sabilunnajat Islamic Boarding School, Cileungsir Village, Rancah District, Ciamis Regency. Islamic boarding schools are one of the alternative institutions in religious science education. Currently, many pesantren educational institutions are widely spread in Indonesia, both in cities and remote villages, but not a few remote students who come from the city or even from the province and across the island. So that differences in customs and language are often a challenge and obstacle for a santri who comes from an area that is quite far away or contrary to the boarding school environment, especially in remote areas. Studying the yellow book is a daily activity for the students, because their goal is to understand its contents and apply their knowledge like their clerics. However, many students have ethnic or linguistic backgrounds that are different from the boarding school environment they live in. Therefore, I took the initiative to apply Indonesian as a language that can be understood by the general public in Islamic boarding school studies, but it does not eliminate the regional language as a language. meaning tool. This makes it easier for students who cannot speak the local language as well as learn the local language.